Angiostrongilíase abdominal: resposta inflamatória tecidual e hematológica em camundongos Swiss - Silva Filho, José Roberto da (2016)
Angiostrongylus costaricensis causes a clinical and anatomopathologic entity named abdominal angiostrongyliasis, and the southern region of Brazil is considered endemic for this pathology. This work aimed to assess the immune response of mice by measuring cytokines and pro-inflammatory cells, and by macro- and microscopic assessment of the lesions of infected animals. The experiment was conducted with 4 groups of infected male Swiss mice, whereas each group had 5 animals; the uninfected control group also consisted of 5 animals and had a 21-day follow-up. Infected animals received 10 third-stage larvae of A. costaricensis. During the experimental period, blood was collected from infected groups at days 3, 7, 14, and 21 through intracardiac puncture, and euthanasia was performed in the respective days. The animals of the control group were euthanized at day 3. Laboratory examinations such as complete blood count were used as assessment parameter of blood cells, and flow cytometry was used to determine and quantify the presence of serum cytokines and to relate the inflammatory process. No significant changes were observed in the complete blood count, and flow cytometry showed an increase in interleukins assessed from day 14. In the anatomopathological diagnosis, the macroscopic assessment of liver, lung, spleen, kidney, and intestine showed no changes. Histopathology showed eosinophilic reactions and/or inflammation in liver, spleen, and intestine (10/20); also granuloma in the intestine wall (1/20) of infected mice. The set of information obtained in this experiment proves that the inflammatory process of infected mice was observed at its initial stage, which may be suggested by complete blood count results. At day 14, histopathology showed intestinal and hepatic eosinophilia in 75% of animals. Interleukins (IL-12p70, IL-6, IL-10, MCP-1, TNF-α, and INF-ɤ) increased at day 21, concomitantly 100% of animals presented intestinal and hepatic eosinophilia. These results allow concluding that understanding mechanisms involving the inflammatory process through cytokines kinetics is related to pathogen defense.